ANALYTIC RAY TRACING FOR THE STUDY OF HF MAGNETO-IONIC RADIO PROPAGATION IN THE IONOSPHERE - Bennett, J. A. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Ray tracing provides a quantitative tool for the study of HF radio wave propagation in the ionosphere, but its use is limited in many applications by the time required to numerically trace many separate rays. One approach to overcoming this problem is the use of ionospheric models that admit analytic solutions of the ray tracing equations. Such a model may be based on a vertical plasma frequency profile consisting of what are known as quasi-parabolic segments. Analytic tracing is much faster than numerical tracing (from 5 to 10 times), but more limited in the range of situations that can be considered. The main thrust of the paper is to present and test a technique, based on the use of an equivalent operating frequency, that allows the analytic results to be extended to take approximate account of the magneto-ionic effects associated with the earth's magnetic field. Errors in group path, phase path and ground range are generally less than 5 km, errors in absorption generally less than 5%. [Vol. 6, No. 1, pp. 192-210 (1991), Special Issue on Applications of High Frequency Methods and Computer Techniques in Elcctromagnetics]